Survival and implantation of indigenous psychrotrophic Oenococcus oeni strains during malolactic fermentation in a Patagonian Pinot noir wine - Manera, Camila (2019)
Spontaneous malolactic fermentation (MLF) in the North Patagonian region of Argentina may have to bear low environmental temperatures, an important stress factor for the lactic acid bacteria (LAB) that conduct this process. Thus, inducing MLF by inoculation of a native starter culture able to lead this biological process at low temperatures is encouraged because it would allow preserving the regional character of the wine. The goal of this work was to obtain autochthonous Oenococcus oeni strains able to consume L-malic acid when MLF takes place at temperatures lower than 15 °C. Among the psychrotrophic isolates obtained from a Pinot noir wine, sixteen O. oeni strains were identified by sequencing the 16S rRNA gene and typing by RAPD PCR, allowing the differentiation of five genotypic groups. After the evaluation of the viability and metabolic performance of the strains in sterile wine at low temperatures, strains UNQOe4 and UNQOe19 were selected to evaluate their behavior in a non-sterile wine at 4 and 10 °C. The strains selected showed good implantation capacity and were able to successfully conduct MLF, suggesting that their use as starter cultures is suitable to improve this biological process in a wine region where environmental temperatures can be low.